Factoring out x
x(-3x^2+15x+42) now factor parenthetical expression
x(-3x^2+21x-6x+42)
x(-3x(x-7)-6(x-7))
x(-3x-6)(x-7) we can factor out -3 from first parentheses
-3x(x+2)(x-7)
Answer:
Step-by-step explanation:
4*(x + 5) + 8x = 4*x + 4*5 + 8x
= 4x + 20 + 8x
= 4x + 8x + 20
= 12x + 20
Answer: 28.5 square units.
Step-by-step explanation: Separate the figure into a rectangle and a triangle. Count the length and width of the rectangle. The length of the rectangle is 8 units and the width is 3 units. To find the area use the formula l*w. 8*3=24.
Next find the area of the triangle section. The triangle is 3 units tall and 3 units wide. To find the area use the formula 1/2(l*w). 3*3=9. 9/2=4.5.
Finally add the areas of the rectangular section and the triangular section. 24+4.5=28.5.
My answer is 12 because I subtract 36 from 24 and got 12
Answer:
Infinite amount of solutions
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality<u>
</u>
<u>Algebra I</u>
- Terms/Coefficients
- Coordinates (x, y)
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define Systems</u>
y = -2x + 4
2x + y = 4
<u>Step 2: Solve for </u><em><u>x</u></em>
<em>Substitution</em>
- Substitute in <em>y</em>: 2x + (-2x + 4) = 4
- Combine like terms: 4 = 4
Here we see that 4 does indeed equal 4.
∴ the systems of equations has an infinite amount of solutions.